AI in Healthcare 5.0: Opportunities and Challenges - Soham.Y.Date; Dr. Meenakshi Thalor (International Journal of Educational and Psychological Sciences, 2023)
AI in Healthcare five.zero represents the next frontier inside the evolution of artificial intelligence within the healthcare enterprise. This paradigm leverages advanced technologies inclusive of quantum computing, augmented reality, and biotechnology to offer exceptional possibilities and confront unique challenges. possibilities include enhanced affected person care through personalised remedy plans, quicker drug discovery, and optimized useful resource allocation. demanding situations encompass moral issues associated with statistics privacy, bias in AI algorithms, and the need for regulatory frameworks to make sure accountable AI deployment. moreover, the integration of AI into healthcare workflows demands substantial investment in infrastructure and team of workers education